Muzara'ah in Efforts for Economic Prosperity: Between Patterns of Behavior, Improvements and Demands - Narastri, Maulidah (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Muzara'ah is known as an agricultural processing cooperation transaction agreement between the land owner and the tenant, where the land owner provides agricultural land and seeds to the cultivator to plant and maintain in return for a certain distribution (percentage) of the harvest. The purpose of this paper is to find out the concept of muzara'ah when viewed from the economic side of natural resources and determine whether muzara'ah is a good system or not. The method of writing this article is a literature study with a literature review approach. The results of the writing show that the muzaraah system has been applied in various agricultural models in the rural area, although some scholars consider it permissible. For readers and writers to study deeper understanding of this muzara'ah and increase references related to it because this practice is still widely practiced by the community.